Implementation of Literation Based Learning Information Technology - Ai Dudu Duriawati; Iim Wasliman; Agus Mulyanto; Ujang Cepi Barlian (International Journal of Nusantara Islam, 2020)
Basic Principles of Digital Literacy Development that digital literacy is a skill that not only involves the ability to use technological devices, information and communication, but also the ability to socialize, the ability to learn, and have the attitude, critical thinking, creative, and inspirational as digital competence. The scope of digital literacy is very broad. Digital literacy can be applied in schools, families and communities. To apply digital literacy in these various areas, different strategies are needed. After getting to know digital literacy, it is hoped that millennials can use technology wisely.